Veterinary anesthetic and monitoring equipment - Cooley, Kristen G.; Johnson, Rebecca A. (Rebecca Ann) (John Wiley & Sons, 2018)
"Veterinary Anesthetic and Monitoring Equipment is the first veterinary-specific resource solely dedicated to anesthetic and monitoring equipment used in clinical practice. • Offers a practical guide to anesthetic and monitoring equipment commonly used in veterinary medicine • Provides clinically oriented guidance to troubleshooting problems that may occur • Discusses general principles applicable to any equipment found in the practice • Presents information associated with novel anesthetic equipment and monitors"